Prinsip Kepentingan Terbaik Bagi Anak Dalam Diversi Pada Sistem Peradilan Pidana Anak - Ni Ketut Wiratny (Jurnal Ilmiah Raad Kertha, 2018)
Article 28 B Paragraph (2), the Constitution of the Republic of IndosesiaYear 1945 each child shall have the right to survival, grow and develop and shallbe entitled to protection of violence and discrimination, Protection of the rights ofthe child shall be contained in the UN Convention on the Rights 1989, has beenratified by more than 191 countries, including Indonesia as a member of the UNthrough Presidential Decree No. 36 of 1990. Thus the UN convention has becomeIndonesian law and binds all Indonesian citizens . To enforce the provisions setforth in the Convention on the Rights of the Child. as well as the basic principles ofthe Convention on the Rights of the Child include: a) discrimination of nonmembers,b) the best interests of the child; c) the right to life, survival anddevelopment; and d) an appreciation of the child's opinion. The best interest of thechild or in English is called the best interests of children is the basic principleunderlying the protection of the child. The best interests of the child should beviewed as 'paramount importance' or top priority. This principle is contained ininternational law and national law related to child protection. The child must beprotected, even if the child is a child in conflict with the law. The principle of thebest interests of the child as set forth in Point 14.2 of The Beijing Rules which statesthat "The proceedings shall be in the atmosphere of understanding, which shallallow the juvenile to participate therein and to express herself or himself freely."(Translation: The process should be done in the best interests of the child andshould be done in an atmosphere of understanding, allowing the child to participatein it and to express himself or herself freely). Within the level of national law, theprinciple of best interests for children is regulated in Article 2 of Law Number 23Year 2002 on Child Protection. The best interest of the child principle reminds allproviders of child protection that consideration in decision-making concerns thechild's future and not retaliation and the placement of imprisonment or childcustody as an ultimate remedy or remedy for ultimate remediation the child'spenalty is not to punish but to educate, restore and recover it as it was before thecrime.